2007
DOI: 10.1371/journal.pmed.0040306
|View full text |Cite
|
Sign up to set email alerts
|

Safe To Walk? Neighborhood Safety and Physical Activity Among Public Housing Residents

Abstract: BackgroundDespite its health benefits, physical inactivity is pervasive, particularly among those living in lower-income urban communities. In such settings, neighborhood safety may impact willingness to be regularly physically active. We examined the association of perceived neighborhood safety with pedometer-determined physical activity and physical activity self-efficacy.Methods and FindingsParticipants were 1,180 predominantly racial/ethnic minority adults recruited from 12 urban low-income housing complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
147
3
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(173 citation statements)
references
References 75 publications
12
147
3
6
Order By: Relevance
“…Adjusted odds ratios (aOR) are adjusted for age, sex, education, race/ethnicity, nativity, income, urbanicity, insurance status, number of visits to the doctor, access to an automobile, duration of diabetes, general health condition and psychological distress of recommended processes of care, but was associated with treatment nonadherence beyond what was explained by individual socioeconomic status, barriers to access to care, and self-reported health. The higher rate of delays in filling prescriptions observed in respondents living in unsafe neighborhoods has not been previously demonstrated in the literature, but is consistent with other work linking neighborhood safety to general health behaviors [21][22][23] and a study linking neighborhood-level socioeconomic disadvantage with adherence to CPAP therapy for obstructive sleep apnea. 32 In the current study, approximately half of the respondents who reported delays in filling prescriptions and obtaining needed care cited cost as the reason for the delay.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Adjusted odds ratios (aOR) are adjusted for age, sex, education, race/ethnicity, nativity, income, urbanicity, insurance status, number of visits to the doctor, access to an automobile, duration of diabetes, general health condition and psychological distress of recommended processes of care, but was associated with treatment nonadherence beyond what was explained by individual socioeconomic status, barriers to access to care, and self-reported health. The higher rate of delays in filling prescriptions observed in respondents living in unsafe neighborhoods has not been previously demonstrated in the literature, but is consistent with other work linking neighborhood safety to general health behaviors [21][22][23] and a study linking neighborhood-level socioeconomic disadvantage with adherence to CPAP therapy for obstructive sleep apnea. 32 In the current study, approximately half of the respondents who reported delays in filling prescriptions and obtaining needed care cited cost as the reason for the delay.…”
Section: Discussionsupporting
confidence: 88%
“…[14][15][16][17][18][19][20] Individuals who live in neighborhoods perceived to be unsafe, for example, report lower levels of physical activity 21 , higher rates of smoking 22,23 , and greater levels of obesity 12 compared to individuals living in neighborhoods perceived to be safe, even after accounting for individual-level markers of socioeconomic status, such as household income. Such "neighborhood effects" on health may be particularly pronounced among individuals with type 2 diabetes, which requires consistent adherence to management regimens that are often challenging and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Neighborhood safety and esthetic appeal have also been associated with rates of physical activity and obesity prevalence in other countries, as public open spaces in unsafe areas may actually discourage physical activity. 55,56 The study is subject to some limitations. First, it is cross-sectional in nature and thus cannot prove causality.…”
Section: Discussionmentioning
confidence: 99%
“…1 Lack of neighborhood safety, defined as perceptions of unsafe neighborhoods as well as objectively measured high-crime neighborhoods have been associated with obesity among both adults and children even after adjusting for socioeconomic factors. [11][12][13] Several studies have noted associations between crime and perceptions of unsafe neighborhoods and low levels of physical among adults and children, 14 with several studies noting associations only among women. 12,15 As women are more often the victims of sexual crimes, they may be more likely to modify their behaviors (i.e., limiting time outdoors engaging in physical activity) if they perceive their environment to be unsafe.…”
Section: Introductionmentioning
confidence: 99%
“…12,15 As women are more often the victims of sexual crimes, they may be more likely to modify their behaviors (i.e., limiting time outdoors engaging in physical activity) if they perceive their environment to be unsafe. 14 crime may be a pathway through which neighborhood crime impacts obesity. Neighborhood safety and crime may also influence social networks and cohesion among neighborhood residents by limiting opportunities for social interaction and promoting distrust among residents.…”
Section: Introductionmentioning
confidence: 99%